Worktime Regulations and Spousal Labor Supply - Goux, Dominique; Maurin, Eric; Petrongolo, Barbara (American Economic Review, 2014)
We study interdependencies in spousal labor supply by exploiting the design of the French workweek reduction, which introduced exogenous variation in one's spouse's labor supply, at constant earnings. Treated employees work on average two hours less per week. Husbands of treated women respond by reducing their labor supply by about half an hour, consistent with substantial leisure complementarity, and specifically cut the nonusual component of their workweek, leaving usual hours unchanged. Women's response to their husband's treatment is instead weak and rarely statistically significant, possibly due to heavier constraints in the organization of their workweek. (JEL J16, J22, K31)